Analysis and modeling of water quality as a contribution to the preliminary framework proposal for the Una River (Pernambuco/Brazil) - Silva,Simone Rosa da (2018)
Abstract The present paper presents a preliminary proposal for a framework for the Una River, located in the state of Pernambuco, divided into prevailing-use classes. This proposal integrates the results of an analysis of water quality parameters and a mathematical modeling performed along a section of the river. Data from six State Environmental Agency (CPRH) monitoring stations were used, which collected data for temperature, pH, DO, BOD, phosphorus, thermotolerant coliforms, turbidity, and color between 2002 and 2014. The mathematical model used was QUAL-UFMG and the parameters evaluated were DO and BOD. The results showed that the DO and BOD parameters were within the limits established by CONAMA Resolution No. 357/2005 for Class 2, but other parameters such as phosphorus presented nonconformities. Based on this, the proposed framework for the Una River covered Classes 1 and 2. It is hoped that such a proposal will serve as a reference for the basin committee in order to discuss and deliberate on the multiple uses preponderant along the river, aiming to approve and implement the framework.